Sikap, Lingkungan Keluarga, Pengetahuan Investasi, dan Niat Mahasiswa Berinvestasi Saham - Julianti, Ni Luh Putu Karisma; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 34 No 2 (2024), 2024)
Investment is the placement of a number of funds at this time to obtain profits in the future. The fact is that currently only a small percentage of students intend to invest. The purpose of this study is to provide empirical evidence regarding the effect of attitudes, family environment, and investment knowledge on students' intentions to invest in stocks. The three independent variables are derived from the theory of planned behavior.This research is located at Udayana University. This study uses quantitative methods. Sampling using purposive sampling methodobtained 154 samples from the research population, namely students of the Faculty of Economics and Business, Udayana University. Data were collected through the distribution of questionnaires. The analysis technique used is multiple linear regression. Theresults of data analysis show that attitudes, family environment, and investment knowledge have an effectpositive on the intention of students to invest in stocks. Keywords:Attitude;Family Environment;Investment Knowledge;Intention